2019
DOI: 10.1002/lno.11111
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Lagrangian transport in Lake Geneva: A 3D numerical modeling investigation

Abstract: Lake Geneva, the largest freshwater lake in Western Europe, is subject to important environmental pressures from its densely populated shores and watershed. To maintain and improve water quality in this lake, as well as in other enclosed or semi-enclosed basins, it is essential to understand and be able to predict how nutrients and pollutants are transported within it. A 3D numerical modeling study of Lagrangian transport in Lake Geneva is presented, showing the dispersion of water (based on tracking inert wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 30 publications
4
41
0
Order By: Relevance
“…The inertial period at the latitude of Lake Geneva is approximately 16.5 hr. Numerous observational and numerical studies have shown that Coriolis force effects play an important role in determining the lake's hydrodynamics (e.g., Bauer et al, 1981; Bouffard & Lemmin, 2013; Cimatoribus et al, 2018, 2019; Lemmin, 2020; Lemmin et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The inertial period at the latitude of Lake Geneva is approximately 16.5 hr. Numerous observational and numerical studies have shown that Coriolis force effects play an important role in determining the lake's hydrodynamics (e.g., Bauer et al, 1981; Bouffard & Lemmin, 2013; Cimatoribus et al, 2018, 2019; Lemmin, 2020; Lemmin et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The particle tracking results also suggest that most of the water masses upwelled in the nearshore area descended back to a maximum depth O(200 m) after the wind stress had ceased (Figures 9d and S5b). The trajectories of these descending water masses were found to be strongly affected by the dynamics of the large-scale motions in the lake, often characterized by large gyres (Cimatoribus et al, 2019), as seen in Figures 9c, 9d, and S5b. Forward particle tracking shows that due to the presence of these large-scale gyres, descending particles rapidly spread over a wide area in the Grand Lac basin, thus demonstrating that coastal upwelling during wintertime, even in a limited nearshore area, is an effective contributor to deepwater renewal over a much larger area.…”
Section: Wintertime Coastal Upwelling As a Pathway For Deepwater Renewalmentioning
confidence: 95%
See 3 more Smart Citations